Diabetes mellitus and cancer risk: Pooled analysis of eight cohort studies in Japan. Issue 11 (25th August 2013) - Sasazuki, Shizuka; Charvat, Hadrien; Hara, Azusa; Wakai, Kenji; Nagata, Chisato; Nakamura, Kozue; Tsuji, Ichiro; Sugawara, Yumi; Tamakoshi, Akiko; Matsuo, Keitaro; Oze, Isao; Mizoue, Tetsuya; et al.
Abstract : Although a growing body of evidence suggests a link between diabetes and cancer, it is not clear whether diabetes independently increases the risk of cancer. We conducted a comprehensive assessment of the association between pre‐existing diabetes and total and site‐specific cancer risk based on a pooled analysis of eight cohort studies in Japan (>330 000 subjects). We estimated a summary hazard ratio by pooling study‐specific hazard ratios for total and site‐specific cancer by using a random‐effects model. A statistically increased risk was observed for cancers at specific sites, such as colon (hazard ratio; HR = 1.40), liver (HR = 1.97), pancreas (HR = 1.85) and bile duct (HR = 1.66; men only). Increased risk was also suggested for other sites, and diabetes mellitus was associated with an overall 20% increased risk in total cancer incidence in the Japanese population. The association between these two diseases has important implications for reiterating the importance of controlling lifestyle factors and may suggest a possible strategy for cancer screening among patients with diabetes. Studies continuously investigating the risk factors for diabetes are also important.